Man-made changes in flora and vegetation: a sketch to a scientific portrait of Professor Herbert Sukopp - Jackowiak, Bogdan (Biodiversity: Research and Conservation, 2020)
The changes in plant cover have been the subject of regular geobotanical research for over 150 years. For several decades, one of the most outstanding researchers of this process has been Professor Herbert Sukopp from the Technische Universität Berlin. This paper discusses the main concepts and most important results of his empirical research. Based on the analysis of international scientific information database resources (Scopus, Web of Science, Google Scholar), the worldwide impact of Sukopp’s publications on the development of research in the field of anthropogenic changes in flora and vegetation was illustrated.